2021
DOI: 10.1161/circulationaha.121.053575
|View full text |Cite
|
Sign up to set email alerts
|

Altered Cardiac Energetics and Mitochondrial Dysfunction in Hypertrophic Cardiomyopathy

Abstract: Background: Hypertrophic cardiomyopathy (HCM) is a complex disease partly explained by the effects of individual gene variants on sarcomeric protein biomechanics. At the cellular level, HCM mutations most commonly enhance force production, leading to higher energy demands. Despite significant advances in elucidating sarcomeric structure-function relationships, there is still much to be learned about the mechanisms that link altered cardiac energetics to HCM phenotypes. In this work, we test the hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
113
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(160 citation statements)
references
References 111 publications
15
113
2
1
Order By: Relevance
“…Together with hypercontractility, this effect may contribute to the inefficient energy usage, which seems to be unequivocally observed in HCM. Here, downstream disturbances in mitochondrial function and metabolic pathways [13,154,208] may exacerbate the situation. Furthermore, both hypercontractility and contractile imbalance (with locally high tension) may stimulate mechanotransductioninitiated signaling pathways in cardiomyocytes (cf.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Together with hypercontractility, this effect may contribute to the inefficient energy usage, which seems to be unequivocally observed in HCM. Here, downstream disturbances in mitochondrial function and metabolic pathways [13,154,208] may exacerbate the situation. Furthermore, both hypercontractility and contractile imbalance (with locally high tension) may stimulate mechanotransductioninitiated signaling pathways in cardiomyocytes (cf.…”
Section: Discussionmentioning
confidence: 99%
“…Additional support for a central role of energy depletion in triggering pathologic HCM remodeling comes from the findings that not only sarcomere protein mutations, but also mutations of key proteins in metabolic pathways, lead to a cardiac phenotype of the HCM type [11,13]. Furthermore, disturbed metabolic signaling and mitochondrial dysfunction seem to be quite central, more generally, in HCM [154]. Here, we do not treat inefficient energy usage or energy depletion as primary effects of the HCM mutations in sarcomere proteins, and the phenomenon is not included among our three key hypotheses (Table 1).…”
Section: Origin and Development Of The Hypercontractility Hypothesismentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it can be assumed that FA pooling is enhanced in hypertrophied myocardium. Ranjbarvaziri et al reported that free FA accumulation in HCM myocardium was significantly higher than that in normal myocardium [ 14 ]. Additionally, they stated that the dysregulation in FA metabolism in HCM myocardium may be caused by mitochondrial damage and reduced citrate synthase activity which was associated with increased reactive oxygen species, based on the findings from electron microscopy and integrated molecular pathway level analysis.…”
Section: Discussionmentioning
confidence: 99%
“…The average fluorescence intensities of mtROS and intracellular ROS were determined using FCM (FACS Aria TM II, BD Bioscience, NJ, China). Transmission electron microscopy (TEM) (suht7700, Hitachi, Japan) was used to examine mitochondrial morphology which was used to examine mitochondrial ultrastructural damage by other researchers [ 25 , 26 ].…”
Section: Methodsmentioning
confidence: 99%